2022
DOI: 10.1101/2022.04.11.22273644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 vaccine coverage among immigrants and refugees in Alberta: a population-based cross-sectional study

Abstract: Introduction: Studies have shown that immigrants have lower vaccination rates than the Canadian-born population. We sought to assess COVID-19 vaccine coverage and factors associated with uptake among foreign-born immigrants relative to the non-immigrant population in Alberta, Canada. Methods: In this cross-sectional study, we analyzed population-based linked administrative health data from Alberta to examine vaccine coverage for 3,931,698 Albertans, of which 731,217 were immigrants. We calculated COVID-19 vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…3,25,26 We found that vaccine coverage increased with both income and population density, and varied by geographic health zone. These relationships are consistent with patterns noted for adult COVID-19 vaccine intention and uptake 27,28 , which is not surprising given that parental vaccination status is highly predictive of vaccination intention for their children. 29 However, the vaccination rate for children in this age group is much lower than that reported for parental-age adults (approximately 90% 2 ).…”
Section: Discussionsupporting
confidence: 82%
“…3,25,26 We found that vaccine coverage increased with both income and population density, and varied by geographic health zone. These relationships are consistent with patterns noted for adult COVID-19 vaccine intention and uptake 27,28 , which is not surprising given that parental vaccination status is highly predictive of vaccination intention for their children. 29 However, the vaccination rate for children in this age group is much lower than that reported for parental-age adults (approximately 90% 2 ).…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, Northeast Calgary (40%) and Northeast Edmonton has a high proportion of immigrant population; it is known that a significant proportion of immigrants are working as front-line workers, who may find social distancing difficult [19,20]. We have previously shown that immigrants in Alberta have higher vaccination coverage than the non-immigrant population, which may also reflect this high-risk employment [21].…”
Section: Plos Onementioning
confidence: 93%
“…(12) Additionally, Northeast Calgary (40%) and Northeast Edmonton have a high proportion of immigrant population; it is known that a significant proportion of immigrants are working as front-line workers, who may find social distancing difficult(14,15) We have previously shown that immigrants in Alberta have higher vaccination coverage than the non-immigrant population, which may also reflect this high risk employment. (16)…”
Section: Discussionmentioning
confidence: 99%